Electrolytic adhesive tape
By using functional copolymers and other raw materials in electrolytic adhesive tape, the existing electrolytic adhesive tape has solved the problems of large ion exudation, insufficient adhesion and residue, and the effects of low ion exudation, high bond strength and easy peeling are achieved, improving the performance and reliability of electronic devices.
Patent Information
- Application Number
- CN202510060700.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-06-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrolytic adhesive tape has problems such as large ion exudation, poor adhesion before power on, and residual after power on, which affects the utilization and protection of electronic devices.
The electrolytic adhesive consisting of functional copolymers, metal lithium salts, surfactants, amphoteric organic ion salts, (3,6-diaminoacridine-9-yl)boric acid and solvents is used to form electrolytic adhesive tapes with low ion exudation, good adhesion and easy peeling through specific hierarchical structures and raw material ratios.
The electrolytic adhesive tape has achieved low ion exudation, high bonding strength before power on, low bonding strength after power on and no residual glue, which improves the utilization and protection of electronic devices.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, and in particular to an electrolytic adhesive tape. Background Art
[0002] In the manufacturing and assembly of electronic components and the repair of electronic equipment, the disassembly and reassembly of electronic equipment components often occurs, and it is necessary to ensure the yield rate and the recycling of used parts. Therefore, the fixation of electronic equipment is inseparable from the use of easy-pull adhesive tape. However, the existing easy-pull adhesive tape has poor adhesion, a high risk of residual adhesive, and is prone to self-cracking or breaking, thereby affecting the quality and efficiency of disassembly and assembly. It is in this situation that electrolytic adhesive tape came into being, and its appearance has attracted widespread attention in the industry.
[0003] Electrolytic adhesive tapes usually contain conductive materials (including cations and anions). When voltage is applied, the conductive materials will undergo an electrolytic reaction. The cations move to the cathode side and undergo a reduction reaction, and the anions move to the anode side and undergo an oxidation reaction, thereby weakening the adhesive interface and making it easy to peel off. However, the cations and anions in this type of adhesive tape are easy to precipitate, which can easily cause problems such as electrical corrosion, unstable properties, and contamination of electronic devices, thereby affecting the use and protection of electronic devices. In addition, the electrolytic adhesive tapes on the market also have more or less technical defects such as poor adhesion before power is applied, and obvious residues on the adhered object after power is applied and debonding.
[0004] In order to solve the above problems, the Chinese invention patent with application publication number CN115895519A discloses an electrolytic adhesive and a double-sided tape, wherein the electrolytic adhesive comprises the following raw material components by weight: 100 parts of adhesive body, 5-30 parts of solid conductive salt, and 5-50 parts of polar aprotic solvent, wherein the solid conductive salt is at least one of ammonium salt, halogenated carbonate and organic sulfonate containing alkali metal; the polar aprotic solvent includes dimethyl carbonate and propylene carbonate. The electrolytic adhesive of the invention increases the conductivity of the adhesive and provides ions that can migrate, thereby reducing the resistance of ion migration. In addition, by selecting at least one of ammonium salt, halogenated carbonate and organic sulfonate containing alkali metal as the solid conductive salt, the adhesion of the electrolytic adhesive tape before power-on can be improved, and the residue on the adhered object after power-on and debonding can be reduced. However, the ion leakage of the tape still needs to be further reduced, and the viscosity reduction effect after power-on still needs to be further improved.
[0005] It can be seen that developing an electrolytic adhesive tape with small ion leakage, good bonding strength before power-on, low bonding strength after power-on, and no residual glue meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the electrolytic adhesive tape field. Summary of the Invention
[0006] The main object of the present invention is to provide an electrolytic adhesive tape with a small ion exudation amount, good bonding strength before energization, low bonding strength after energization, and no residual glue.
[0007] To achieve the above object, the present invention provides an electrolytic adhesive tape, which sequentially includes a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer, and a second release film layer from top to bottom; the first electrolytic adhesive layer and the second electrolytic adhesive layer independently include the following raw materials in parts by weight: 100 parts of a functional copolymer, 6-15 parts of a metal lithium salt, 1-2 parts of a surfactant, 4-6 parts of an amphoteric organic ion salt, 3-5 parts of (3,6-diaminoacridin-9-yl)boronic acid, 0.3-1 part of a leveling agent, and 30-50 parts of a solvent; the functional copolymer includes structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
[0008] Preferably, the preparation method of the functional copolymer includes the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and an initiator into a high-boiling solvent, stirring and reacting at 60-70°C for 3-5 h in an inert gas atmosphere, precipitating in water after the reaction, washing the precipitated polymer with ethanol 3-6 times, and finally drying it in a vacuum drying oven at 85-95°C to constant weight to obtain the functional copolymer.
[0009] Preferably, the mass ratio of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, the initiator, and the high-boiling solvent is 1:(0.8-1.2):(1-3):(0.03-0.05):(10-20).
[0010] Preferably, the initiator is azobisisobutyronitrile.
[0011] Preferably, the high-boiling solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone.
[0012] Preferably, the inert gas is any one of nitrogen, helium, neon, and argon.
[0013] Preferably, the lithium metal salt is at least one of lithium tetrafluoroborate, lithium trifluoromethanesulfonate, and lithium tris(trifluoromethanesulfonyl)methyl.
[0014] Preferably, the surfactant is one or a combination of two or more of Span 80, Tween 20, sodium dodecylbenzenesulfonate, and lauramidopropyl betaine.
[0015] Preferably, the zwitterionic organic salt is at least one of pyridinium hydroxypropanesulfonate and 1-benzylpyridinium-3-carboxylate.
[0016] Preferably, the leveling agent is leveling agent BYK358N.
[0017] Preferably, the solvent is dimethyl carbonate.
[0018] Preferably, the thickness of the aluminum foil substrate is 10-15 μm.
[0019] Preferably, both the first release film and the second release film are polyethylene terephthalate release films; the thickness of the first release film layer is 20-30 μm; the thickness of the second release film layer is 20-30 μm.
[0020] Preferably, the thickness of the first electrolytic adhesive layer is 5-10 μm; the thickness of the second electrolytic adhesive layer is 5-10 μm.
[0021] Another object of the present invention is to provide a method for preparing the electrolytic adhesive tape, comprising the following steps: Step S1: Mix the functional copolymer, lithium metal salt, surfactant, zwitterionic organic salt, (3,6-diaminoacridin-9-yl)boric acid, leveling agent, and solvent uniformly to obtain an electrolytic adhesive. Step S2: Coat the electrolytic adhesive on the upper and lower surfaces of the aluminum foil substrate, dry it at 90-100 °C for 5-8 min to obtain a first electrolytic adhesive layer and a second electrolytic adhesive layer respectively; then attach the first release film to the upper surface of the first electrolytic adhesive layer, and attach the second release film to the lower surface of the second electrolytic adhesive layer to obtain the electrolytic adhesive tape.
[0022] Due to the application of the above technical solutions, the present invention has the following beneficial effects: (1)The preparation method of the electrolytic adhesive tape disclosed by the present invention is simple and easy to implement, convenient to operate and control, with high preparation efficiency and high qualified rate of finished products, low dependence on equipment, suitable for continuous large-scale production, and has high popularization and application value.
[0023] (2)For the electrolytic adhesive tape disclosed by the present invention, the first electrolytic adhesive layer and the second electrolytic adhesive layer independently comprise the following raw materials in parts by weight: 100 parts of functional copolymer, 6 - 15 parts of metal lithium salt, 1 - 2 parts of surfactant, 4 - 6 parts of zwitterionic organic salt, 3 - 5 parts of (3,6-diaminoacridin-9-yl)boronic acid, 0.3 - 1 part of leveling agent, and 30 - 50 parts of solvent; the functional copolymer comprises the structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide. Through the mutual cooperation and joint action of the raw materials, the prepared electrolytic adhesive tape has a small ion exudation amount, good bonding strength before electrification, low bonding strength after electrification, and no residual glue after peeling; the introduction of zwitterionic salt structure into the adhesive substrate interacts with the freely movable zwitterionic salt added in the adhesive, improving the problems of large ion exudation amount and poor performance stability without affecting the conductivity.
[0024] (3)For the electrolytic adhesive tape disclosed by the present invention, the amino group on (3,6-diaminoacridin-9-yl)boronic acid can undergo an epoxy ring-opening reaction with the epoxy group introduced in the functional copolymer to form an interpenetrating network structure. And through the reasonable selection of raw materials and copolymerization monomers, zwitterionic organic salt, triazine ketone, cyano group, trifluoromethylphenyl group, amide group, hydroxyl group, amino group, and boronic acid group structures are simultaneously introduced into the adhesive. Under the multiple effects of electronic effect, steric effect, and conjugate effect, these structures can effectively improve the bonding strength before electrification and reduce the ion exudation amount; through molecular structure design, the adhesive can form a unique ion channel after electrification, with anions moving towards the positive electrode and cations moving towards the negative electrode, resulting in phase separation and wrinkles at the interface bonded to the adherend, destroying the bonding interface. At the same time, an oxidation reaction occurs at the interface of the metal adherend connected to the positive electrode of the power supply (if the adherend is non-conductive, a conductive layer can be formed by surface printing conductive ink, and this interface is the interface of the conductive layer on the adherend), forming metal cations. In this way, negative ions also need to migrate to this interface to compensate for these metal cations. The slight oxidation of the metal of the adherend at the positive electrode will also cause a change in the interface morphology and promote the debonding at the interface; thus, the electrolytic adhesive tape can be peeled off as needed after electrification, with low bonding strength after electrification and no residual glue after peeling, so as to realize the repair or recycling of the bonded parts. Detailed implementation mode
[0025] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments in the following description are only examples, and other obvious variations can be thought of by those skilled in the art. Example 1
[0026] An electrolytic adhesive tape, which sequentially includes a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer, and a second release film layer from top to bottom; the first electrolytic adhesive layer and the second electrolytic adhesive layer independently include the following raw materials in parts by weight: 100 parts of a functional copolymer, 6 parts of a metal lithium salt, 1 part of a surfactant, 4 parts of an amphoteric organic ionic salt, 3 parts of (3,6-diaminoacridin-9-yl)boronic acid, 0.3 part of a leveling agent, and 30 parts of a solvent; the functional copolymer includes structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
[0027] The preparation method of the functional copolymer includes the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and an initiator into a high-boiling solvent, stirring and reacting at 60°C for 3 h in an inert gas atmosphere, precipitating in water after the reaction, washing the precipitated polymer with ethanol 3 times, and finally drying it to constant weight at 85°C in a vacuum drying oven to obtain the functional copolymer; the mass ratio of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, the initiator, and the high-boiling solvent is 1:0.8:1:0.03:10; the initiator is azobisisobutyronitrile; the high-boiling solvent is dimethyl sulfoxide; the inert gas is nitrogen; through GPC testing, the M n = 14680 g / mol, M W / M n= 1.359; Through elemental analysis and weight change calculation, the mass ratios of the structural units introduced by 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and N-(4-cyano-3-trifluoromethylphenyl)methacrylamide in the functional copolymer are 0.98:0.8:0.99 respectively.
[0028] The lithium metal salt is lithium tetrafluoroborate; the surfactant is Span 80; the zwitterionic organic salt is pyridinium hydroxypropanesulfonate; the leveling agent is leveling agent BYK358N; the solvent is dimethyl carbonate.
[0029] The thickness of the aluminum foil substrate is 10 μm; the first release film and the second release film are both polyethylene terephthalate release films; the thickness of the first release film layer is 20 μm; the thickness of the second release film layer is 20 μm; the thickness of the first electrolytic adhesive layer is 5 μm; the thickness of the second electrolytic adhesive layer is 5 μm.
[0030] A preparation method of the electrolytic adhesive tape includes the following steps: Step S1: Mix the functional copolymer, lithium metal salt, surfactant, zwitterionic organic salt, (3,6-diaminoacridin-9-yl)boric acid, leveling agent, and solvent evenly to obtain an electrolytic adhesive. Step S2: Coat the electrolytic adhesive on the upper and lower surfaces of the aluminum foil substrate, dry it at 90 °C for 5 min to obtain the first electrolytic adhesive layer and the second electrolytic adhesive layer respectively; then attach the first release film to the upper surface of the first electrolytic adhesive layer and attach the second release film to the lower surface of the second electrolytic adhesive layer to obtain the electrolytic adhesive tape. Example 2
[0031] An electrolytic adhesive tape, which sequentially includes a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer, and a second release film layer from top to bottom; the first electrolytic adhesive layer and the second electrolytic adhesive layer independently include the following raw materials in parts by weight: 100 parts of a functional copolymer, 8 parts of a metal lithium salt, 1.2 parts of a surfactant, 4.5 parts of an amphoteric organic ion salt, 3.5 parts of (3,6-diaminoacridin-9-yl)boronic acid, 0.5 part of a leveling agent, and 35 parts of a solvent; the functional copolymer includes structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
[0032] The preparation method of the functional copolymer includes the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and an initiator into a high-boiling solvent, stirring and reacting at 63 °C under an inert gas atmosphere for 3.5 h, precipitating in water after the reaction, washing the precipitated polymer with ethanol 4 times, and finally drying it to constant weight at 88 °C in a vacuum drying oven to obtain the functional copolymer; the mass ratio of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, the initiator, and the high-boiling solvent is 1:0.9:1.5:0.035:13; the initiator is azobisisobutyronitrile; the high-boiling solvent is N,N-dimethylformamide; the inert gas is helium; the metal lithium salt is lithium trifluoromethanesulfonate; the surfactant is Tween 20; the amphoteric organic ion salt is 1-benzylpyridin-3-carboxylate; the leveling agent is leveling agent BYK358N; the solvent is dimethyl carbonate.
[0033] The thickness of the aluminum foil substrate is 10 μm; both the first release film and the second release film are polyethylene terephthalate release films; the thickness of the first release film layer is 20 μm; the thickness of the second release film layer is 20 μm; the thickness of the first electrolytic adhesive layer is 5 μm; the thickness of the second electrolytic adhesive layer is 5 μm.
[0034] A preparation method of the electrolytic adhesive tape comprises the following steps: Step S1: After uniformly mixing a functional copolymer, a lithium metal salt, a surfactant, an amphoteric organic ion salt, (3,6-diaminoacridin-9-yl)boronic acid, a leveling agent and a solvent, an electrolytic adhesive is obtained; Step S2: The electrolytic adhesive is coated on the upper and lower surfaces of an aluminum foil substrate and dried at 93 °C for 6 min to obtain a first electrolytic adhesive layer and a second electrolytic adhesive layer respectively; then a first release film is laminated on the upper surface of the first electrolytic adhesive layer, and a second release film is laminated on the lower surface of the second electrolytic adhesive layer to obtain the electrolytic adhesive tape. Example 3
[0035] An electrolytic adhesive tape successively comprises a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer and a second release film layer from top to bottom; the first electrolytic adhesive layer and the second electrolytic adhesive layer independently comprise the following raw materials in parts by weight: 100 parts of a functional copolymer, 10 parts of a lithium metal salt, 1.5 parts of a surfactant, 5 parts of an amphoteric organic ion salt, 4 parts of (3,6-diaminoacridin-9-yl)boronic acid, 0.6 part of a leveling agent and 40 parts of a solvent; the functional copolymer comprises structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
[0036] The preparation method of the functional copolymer comprises the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and an initiator into a high-boiling solvent, stirring and reacting at 65 °C for 4 h under an inert gas atmosphere, precipitating in water after the reaction, washing the precipitated polymer with ethanol 5 times, and finally drying to constant weight at 90 °C in a vacuum drying oven to obtain the functional copolymer; the mass ratio of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, the initiator, and the high-boiling solvent is 1:1:2:0.04:15; the initiator is azobisisobutyronitrile; the high-boiling solvent is N-methylpyrrolidone; the inert gas is neon.
[0037] The metal lithium salt is lithium tris(trifluoromethanesulfonyl)methide; the surfactant is sodium dodecylbenzenesulfonate; the zwitterionic organic salt is pyridinium hydroxypropanesulfonate; the leveling agent is leveling agent BYK358N; the solvent is dimethyl carbonate.
[0038] The thickness of the aluminum foil substrate is 10 μm; the first release film and the second release film are both polyethylene terephthalate release films; the thickness of the first release film layer is 20 μm; the thickness of the second release film layer is 20 μm; the thickness of the first electrolytic adhesive layer is 5 μm; the thickness of the second electrolytic adhesive layer is 5 μm.
[0039] A preparation method of the electrolytic adhesive tape comprises the following steps: Step S1: Mix the functional copolymer, the metal lithium salt, the surfactant, the zwitterionic organic salt, (3,6-diaminoacridin-9-yl)boronic acid, the leveling agent, and the solvent evenly to obtain an electrolytic adhesive; Step S2: Coat the electrolytic adhesive on the upper and lower surfaces of the aluminum foil substrate, dry at 95 °C for 6.5 min to obtain a first electrolytic adhesive layer and a second electrolytic adhesive layer respectively; then attach the first release film to the upper surface of the first electrolytic adhesive layer, and attach the second release film to the lower surface of the second electrolytic adhesive layer to obtain the electrolytic adhesive tape. Example 4
[0040] An electrolytic adhesive tape, which sequentially includes a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer, and a second release film layer from top to bottom; the first electrolytic adhesive layer and the second electrolytic adhesive layer independently include the following raw materials by weight: 100 parts of a functional copolymer, 13 parts of a metal lithium salt, 1.8 parts of a surfactant, 5.5 parts of an amphoteric organic ion salt, 4.5 parts of (3,6-diaminoacridin-9-yl)boronic acid, 0.9 part of a leveling agent, and 45 parts of a solvent; the functional copolymer includes structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
[0041] The preparation method of the functional copolymer includes the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and an initiator into a high-boiling solvent, stirring and reacting at 68 °C in an inert gas atmosphere for 4.5 h, precipitating in water after the reaction, washing the precipitated polymer with ethanol 5 times, and finally drying it to constant weight at 93 °C in a vacuum drying oven to obtain the functional copolymer; the mass ratio of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, the initiator, and the high-boiling solvent is 1:1.1:2.5:0.045:18; the initiator is azobisisobutyronitrile; the high-boiling solvent is a mixture of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone in a mass ratio of 1:2:3; the inert gas is argon; the metal lithium salt is a mixture of lithium tetrafluoroborate, lithium trifluoromethanesulfonate, and lithium tris(trifluoromethanesulfonyl)methyl in a mass ratio of 1:2:1.
[0042] The surfactant is a mixture of Span 80, Tween 20, sodium dodecylbenzenesulfonate, and lauramidopropyl betaine in a mass ratio of 1:3:5:2; the amphoteric organic ion salt is a mixture of hydroxypropane sulfonic acid pyridine salt and 1-benzylpyridine-3-carboxylate in a mass ratio of 3:5; the leveling agent is leveling agent BYK358N; the solvent is dimethyl carbonate.
[0043] The thickness of the aluminum foil substrate is 10 μm; both the first release film and the second release film are polyethylene terephthalate release films; the thickness of the first release film layer is 20 μm; the thickness of the second release film layer is 20 μm; the thickness of the first electrolytic adhesive layer is 5 μm; the thickness of the second electrolytic adhesive layer is 5 μm.
[0044] A preparation method of the electrolytic adhesive tape includes the following steps: Step S1: Mix a functional copolymer, a metal lithium salt, a surfactant, an amphoteric organic ion salt, (3,6-diaminoacridin-9-yl)boronic acid, a leveling agent, and a solvent evenly to obtain an electrolytic adhesive. Step S2: Coat the electrolytic adhesive on the upper and lower surfaces of the aluminum foil substrate, and dry it at 98 °C for 7.5 min to obtain a first electrolytic adhesive layer and a second electrolytic adhesive layer respectively; then attach the first release film to the upper surface of the first electrolytic adhesive layer, and attach the second release film to the lower surface of the second electrolytic adhesive layer to obtain the electrolytic adhesive tape. Example 5
[0045] An electrolytic adhesive tape includes, from top to bottom in sequence, a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer, and a second release film layer; the first electrolytic adhesive layer and the second electrolytic adhesive layer independently include the following raw materials in parts by weight: 100 parts of a functional copolymer, 15 parts of a metal lithium salt, 2 parts of a surfactant, 6 parts of an amphoteric organic ion salt, 5 parts of (3,6-diaminoacridin-9-yl)boronic acid, 1 part of a leveling agent, and 50 parts of a solvent; the functional copolymer includes structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
[0046] The preparation method of the functional copolymer comprises the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and an initiator into a high-boiling solvent, stirring and reacting at 70 °C for 5 h under an inert gas atmosphere, precipitating in water after the reaction, washing the precipitated polymer with ethanol 6 times, and finally drying it to constant weight at 95 °C in a vacuum drying oven to obtain the functional copolymer; the mass ratio of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, the initiator, and the high-boiling solvent is 1:1.2:3:0.05:20; the initiator is azobisisobutyronitrile; the high-boiling solvent is dimethyl sulfoxide; the inert gas is nitrogen; the metal lithium salt is lithium tetrafluoroborate; the surfactant is lauramidopropyl betaine; the zwitterionic organic salt is pyridinium hydroxypropanesulfonate; the leveling agent is leveling agent BYK358N; the solvent is dimethyl carbonate.
[0047] The thickness of the aluminum foil substrate is 10 μm; both the first release film and the second release film are polyethylene terephthalate release films; the thickness of the first release film layer is 20 μm; the thickness of the second release film layer is 20 μm; the thickness of the first electrolytic adhesive layer is 5 μm; the thickness of the second electrolytic adhesive layer is 5 μm.
[0048] A preparation method of the electrolytic adhesive tape comprises the following steps: Step S1: Mix the functional copolymer, metal lithium salt, surfactant, zwitterionic organic salt, (3,6-diaminoacridin-9-yl)boric acid, leveling agent, and solvent evenly to obtain an electrolytic adhesive. Step S2: Coat the electrolytic adhesive on the upper and lower surfaces of the aluminum foil substrate, dry it at 100 °C for 8 min to obtain the first electrolytic adhesive layer and the second electrolytic adhesive layer respectively; then laminate the first release film on the upper surface of the first electrolytic adhesive layer, and laminate the second release film on the lower surface of the second electrolytic adhesive layer to obtain the electrolytic adhesive tape.
[0049] Comparative Example 1 An electrolytic adhesive tape is basically the same as that in Example 1, except that 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonate inner salt is not added.
[0050] Comparative Example 2 An electrolytic adhesive tape is substantially the same as Example 1, except that no amphoteric organic ion salt is added and an equal amount of ethylenediamine is used instead of (3,6-diaminoacridine-9-yl)boric acid.
[0051] In order to further illustrate the beneficial technical effects of the electrolytic adhesive tape involved in each embodiment of the present invention, relevant performance tests were carried out on the electrolytic adhesive tape involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the release film of the electrolytic adhesive tape prepared in each example was torn off, and it was attached to the electric vehicle battery pack. A 2kg rubber roller was used to press it back and forth 3 times, and the release film on the other side was torn off. The electric vehicle battery pack was fixed on the electric vehicle and placed at 23°C for 24 hours before testing.
[0052] Peel force test before power on: The peel force of the electrolytic adhesive tape prepared in each example was tested according to GB / T2792-2014 standard.
[0053] Peel force test after power-on: The electrolytic adhesive tape attached to the electric vehicle battery pack is powered on (voltage is 30V), and the peel force of the electrolytic adhesive tape after power-on is tested in accordance with GB / T2792-2014 standard, and the surface of the electric vehicle battery pack is observed to see if there is any residual adhesive and the debonding time is recorded.
[0054] Peel force retention rate (%): After the above-mentioned peel force test after power-on is completed, the electrolytic adhesive tape is peeled off and then applied to the stainless steel plate and the electric vehicle battery pack again, and pressed back and forth 3 times with a 2kg rubber roller in an environment of room temperature and humidity; after 30 minutes, the peel force before power-on is measured again, and the peel force retention rate is calculated. The larger the value, the smaller the ion leakage and the better the recovery.
[0055] As can be seen from Table 1, the electrolytic adhesive tape disclosed in the embodiment of the present invention has better bonding strength before power-on, more excellent electrolytic bonding effect and recovery than the comparative example product; the combined use of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, amphoteric organic ion salt, and (3,6-diaminoacridine-9-yl)boric acid is beneficial to improving the above-mentioned properties.
[0056] Table 1
[0057] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and what is described in the above embodiments and the specification is only the principle of the present invention. Without departing from the spirit and scope of the present invention, various changes and improvements will occur to the present invention, and these changes and improvements fall within the scope of the present invention claimed. The scope of protection required by the present invention is defined by the appended claims and their equivalents.
Claims
1. An electrolytic adhesive tape, characterized in that: From top to bottom, it includes a first release film layer, a first electrolytic adhesive layer, an aluminum foil substrate layer, a second electrolytic adhesive layer, and a second release film layer; the first electrolytic adhesive layer and the second electrolytic adhesive layer are independently made of the following raw materials in parts by weight: 100 parts of functional copolymer, 6-15 parts of metal lithium salt, 1-2 parts of surfactant, 4-6 parts of amphoteric organic ion salt, 3-5 parts of (3,6-diaminoacridine-9-yl) boric acid, 0. 3-1 parts, 30-50 parts of solvent; the functional copolymer includes structural units introduced by the following monomers: 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and N-(4-cyano-3-trifluoromethylphenyl)methacrylamide.
2. The electrolytic adhesive tape according to claim 1, characterized in that: The preparation method of the functional copolymer comprises the following steps: adding 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide and an initiator into a high boiling point solvent, stirring and reacting for 3-5 hours at 60-70° C. in an inert gas atmosphere, precipitating the polymer in water after the reaction is completed, washing the precipitated polymer with ethanol for 3-6 times, and finally drying the polymer in a vacuum drying oven at 85-95° C. to a constant weight to obtain the functional copolymer.
3. The electrolytic adhesive tape according to claim 2, characterized in that: The mass ratio of the 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, initiator, and high boiling point solvent is 1:(0.8-1.2):(1-3):(0.03-0.05):(10-20).
4. The electrolytic adhesive tape according to claim 2, characterized in that: The initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.
5. The electrolytic adhesive tape according to claim 1, characterized in that: The metal lithium salt is at least one of lithium tetrafluoroborate, trifluoromethylsulfonyl lithium, and tris(trifluoromethylsulfonyl)methyl lithium; the surfactant is one of Span 80, Tween 20, sodium dodecylbenzenesulfonate, and lauroylamidopropyl betaine, or a combination of two or more thereof.
6. The electrolytic adhesive tape according to claim 1, characterized in that: The amphoteric organic ion salt is at least one of hydroxypropane sulfonate pyridinium salt and 1-benzylpyridine-3-carboxylate; the leveling agent is leveling agent BYK358N; and the solvent is dimethyl carbonate.
7. The electrolytic adhesive tape according to claim 1, characterized in that: The thickness of the aluminum foil substrate is 10-15 μm; the first release film and the second release film are both polyethylene terephthalate release films; the thickness of the first release film layer is 20-30 μm; the thickness of the second release film layer is 20-30 μm; the thickness of the first electrolytic adhesive layer is 5-10 μm; the thickness of the second electrolytic adhesive layer is 5-10 μm.
8. A method for preparing the electrolytic adhesive tape according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, mixing the functional copolymer, the metal lithium salt, the surfactant, the amphoteric organic ion salt, (3,6-diaminoacridine-9-yl)boric acid, the leveling agent and the solvent uniformly to obtain an electrolytic adhesive; Step S2, coating the electrolytic adhesive on the upper and lower surfaces of the aluminum foil substrate, and drying at 90-100°C for 5-8 minutes to obtain a first electrolytic adhesive layer and a second electrolytic adhesive layer, respectively; then laminating the first release film on the upper surface of the first electrolytic adhesive layer, and laminating the second release film on the lower surface of the second electrolytic adhesive layer to obtain an electrolytic adhesive tape.
Citation Information
Patent Citations
Electrolytic adhesive and double-sided tape
CN115895519A
Cited By
Alkali-free accelerator and preparation method thereof
CN120040107A
